Information systems for crisis response and management in Mediterranean Countries : 4th International Conference, ISCRAM-med 2017, Xanthi, Greece, October 18-20, 2017, Proceedings - Dokas, Ioannis M.; Bellamine-Ben Saoud, Narjès; Dugdale, Julie; Díaz, Paloma (Springer, 2017)
This book constitutes the refereed proceedings of the 4th International Conference on Information Systems for Crisis Response and Management in Mediterranean Countries, ISCRAM-med 2017, held in Xanthi, Greece, in October 2017. ISCRAM-med conferences aim to enhance the collaboration and solidarity between Mediterranean countries in issues related to crisis management. They offer an outstanding opportunity to address and discuss new trends and challenges in the area of Information systems and Technologies for Crisis Response and Management (ISCRAM). The 12 full and 5 short papers presented in this volume were carefully reviewed and selected from 39 submissions. They were organized in topical sections named: social networking and big data analytics; robotic systems for crisis management; decision making in the context of crisis management; serious games and simulations; and collaboration and information sharing.
Keywords: Emergency management -- Data processing -- Congresses.; Information technology -- Congresses.; elektronické knihy; electronic books